Topikal ASI Mempercepat Pemutusan Tali Pusat - Susilawati, Elly; Fathunikmah, Fathunikmah; Ilma, Intan Nurul (JURNAL IBU DAN ANAK, 2022)
The occurrence of umbilical cord infections causes the mortality and morbidity of infants in developing countries to increase with an incidence rate of 55 - 197 per 1000 live births. The purpose of this study was to determine the effect of topical breastfeeding on the time of umbilical cord release. This study is a true experiment with a post test only control design. Respondents in this study were 20 newborn babies who would be divided into 2 groups, namely 10 respondents in the treatment group and 10 respondents in the control group. The sample selection using purposive sampling technique. The results of the study in the group given topical breastfeeding was 3.30 days while the group who was not given topical breastfeeding was 5.70 days. From these mean values ​​it was seen that the umbilical cord release was faster in the treatment group. Mann-Whitney test results showed the effect of topical breastfeeding on the time of umbilical cord release (p = 0.015).